Tree rings provide snapshots of earth's past climate / Nur Idzhainee Hashim, Firdaus Chek Sulaiman and Ahmad Nazrin Aris Anuar - Hashim, Nur Idzhainee; Chek Sulaiman, Firdaus; Anuar, Ahmad Nazrin Aris (College of Built Environment, 2023)
Dendrochronology is the scientific discipline of determining the relationship between tree growth and climate, and is determined using the annual growth rings.